An evaluation of the reproducibility of capacitive sensor based in-plane permeability measurements: A benchmarking study - H. Groessing; D. Becker; S. Kaufmann; R. Schledjewski; P. Mitschang (eXPRESS Polymer Letters)
A benchmark study for permeability measurement is presented. In the past studies of other research groups which focused on the reproducibility of 1D-permeability measurements showed high standard deviations of the gained permeability values (25%), even though a defined test rig with required specifications was used. Within this study, the reproducibility of capacitive in-plane permeability testing system measurements was benchmarked by comparing results of two research sites using this technology. The reproducibility was compared by using a glass fibre woven textile and carbon fibre non crimped fabric (NCF). These two material types were taken into consideration due to the different electrical properties of glass and carbon with respect to dielectric capacitive sensors of the permeability measurement systems. In order to determine the unsaturated permeability characteristics as function of fibre volume content the measurements were executed at three different fibre volume contents including five repetitions. It was found that the stability and reproducibility of the presentedin-plane permeability measurement system is very good in the case of the glass fibre woven textiles. This is true for the comparison of the repetition measurements as well as for the comparison between the two different permeameters. These positive results were confirmed by a comparison to permeability values of the same textile gained with an older generation permeameter applying the same measurement technology. Also it was shown, that a correct determination of the grammage and the material density are crucial for correct correlation of measured permeability values and fibre volume contents.